First Record of a Rare New Species of Dracognomus (Nematoda: Draconematidae) from the Northwest Pacific Ocean - Seungyeop Han; Hyun Soo Rho (Diversity)
We report the discovery of a novel free-living marine nematode, Dracognomus elongatus sp. nov., from the genus Dracognomus Allen & Noffsinger, 1978 (Nematoda: Draconematidae), collected from geniculate coralline algal assemblages in the intertidal zone along the eastern coast of Korea in the Northwest Pacific Ocean. Dracognomus elongatus sp. nov. is distinguished from its congeners by several key features: a relatively long body length (522 µm), densely developed minute spine-like ornamentation along the margins of body annules, small pore-shaped amphids (2 µm) with membranous tubes filled with corpus gelatum extending to the fifth body annule, twelve modified cephalic adhesion tubes located posterior to the rostrum, eight pairs of modified adhesion tubes in the mid-body region, an arrangement of both normal and modified subventral adhesion tubes (three pairs of each), disc-shaped tips on sublateral adhesion tubes, absence of copulatory thorns in males, and the presence of three pairs of short setae with no protuberances on the non-annulated tail end. Morphological details and illustrations were obtained using differential interference contrast microscopy. We also provide information on the geographic distribution and comparative characteristics of species within the genus Dracognomus, along with a schematic ventral view of a congener illustrating the arrangement of posterior adhesion tubes and copulatory thorns. Additionally, we present a species-level pictorial dichotomous key. Dracognomus elongatus sp. nov. is the eighth described species of this rare genus and marks the first record of Dracognomus in the Northwest Pacific Ocean.